Edukasi Self-Care Management untuk Mengatasi Nyeri Punggung Bawah di Desa Tanjung Anom - Diah Karlina (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Low Back Pain (LBP) is a complaint characterized by pain or discomfort felt in the lower back, which may radiate to the legs, either the right or left leg. Prolonged sitting can cause tension in the lower back muscles, eventually leading to pain. This activity aims to educate the batik artisan community on self-care methods to manage low back pain and correct sitting positions while working as batik artisans. The target of this activity is the batik artisans in Dusun 1 and Dusun 6 of Tanjung Anom Village. The method used in this program involved students conducting direct field observations, engaging in dialogue, and interviewing batik artisans using screening forms with a sample size of 20 artisans. The results showed that the majority of batik artisans in Dusun 1, Tanjung Anom Village, complained of low back pain. The conclusion of this activity is that a monotonous working position significantly affects the incidence of low back pain, especially among batik artisans.